Do Woody Tree Thinning and Season Have Effect on Grass Species’ Composition and Biomass in a Semi-Arid Savanna? The Case of a Semi-Arid Savanna, Southern Ethiopia - Hare, Malicha Loje; Xu, Xin Wen; Wang, Yong Dong; Yuan, You; Gedda, Abule Ebro (Frontiers in Environmental Science, 2021)
Encroachment of woody plants has negative effects on grass species and seriously challenging livestock production and pastoral livelihood in semi-arid savanna. The effect of thinning and season on grass species composition and biomass was investigated in lowland grazing area for three seasons. The study consisted of 15 plots (each 50m × 50m), thinned to differing intensities. The plots were located next to each other on a homogeneous area of 3.8 ha. Five thinning intensities (0%, 25%, 50%, 75% and 100%) were allocated randomly to the plots and replicated three times. The 0% plot was left unthinned referred to as the control plot. The remaining plots were thinned to the equivalents of 25%, 50%, 75% and 100% of the tree density of that of the control plot. A two-way analysis of variance and Tukey Honest Significant Differences tests were used to compare responses of grass species. Ordination of variables was carried out by multivariate technique using correspondence analysis to explore the similarity relationship of plots, seasons and species. The differences in species composition and biomass in the control and the thinned plots were significant (p < 0.05). Higher grass species composition and biomass were documented in thinned plots than in the control plot. Species abundance in thinned plots ranged from 11-12, while that of the 0% plot was 6 species. Grass biomass (Kg ha-1) varied from 2688.4 ± 736.8 - 5035.8 ± 743.9 across thinned plots, whereas in the control plot the yield was 885.8 ± 369.1. The result showed that grass species composition and biomass increased with the increasing intensity of thinning. Grass values appeared to be optimum at the heavy intensity of thinning woody plants. Seasons were also significant with the highest values recorded in the rainy season. Rainfall played an important role by interacting with thinning and influenced total grass values. Overall, thinning that combined improved soil moisture negatively influenced woody cover and enhanced grass species composition and biomass production. Thinning of bushes to the 75% of tree density would sustain the original savanna and maximize forage production for grazers. Keywords: thinning, Acacia drepanolobium, grass, species composition, biomass.